The Sociodemographic Profile of Indonesia’s Top 5 Biggest Chronic Disease: an IFLS 2014 Analysis - Pauline Natania Tanjaya; Pudji Lestari; Johanes Nugroho Ekoputranto (Universitas Airlangga, 2026)
Due to the drastic transformation in many sectors of life and its population characteristics, chronic diseases have become one of the biggest causes of death in Indonesia. Various speculations have been made on the demographics at risk of chronic diseases. To that end, this study aims to capture the sociodemographic profiles of the 5 most prevalent chronic diseases in Indonesia, using data from the 2014 Indonesian Family Life Survey (IFLS). Analysis is conducted by processing data from the designated books of the 2014 IFLS 5 with SPSS. The acquired results show that most respondents suffer from hypertension, are female, and are within the span of 30 to 50 years old. More women suffer from cancer and hypertension than men, while more men suffer from heart diseases and diabetes. Most respondents come from Java and are Javanese. They mostly make up the private and government workforce and have higher incomes, in contrast to the majority low- to middle-income population of Indonesia. There are various explanations for this phenomenon, namely a longer life expectancy and more common preventive health behaviors among women, as well as biological and environmental factors that contribute to the different manifestations among men and women. Further research could be done to construct a modern-day sociodemographic profile and investigate the aforementioned phenomenon.